1998
DOI: 10.1038/nm0398-285
|View full text |Cite
|
Sign up to set email alerts
|

In vivo site-directed mutagenesis of the factor IX gene by chimeric RNA/DNA oligonucleotides

Abstract: A chimeric RNA/DNA oligonucleotide was constructed to induce a sequence mutation in the rat factor IX gene, resulting in prolonged coagulation. Oligonucleotides were targeted to hepatocytes in cell culture or in vivo by intravenous injection. Nucleotide conversion was both site-specific and dose-dependent. The mutated gene was associated in vivo with significantly reduced factor IX coagulant activity and a marked prolongation of the activated partial thromboplastin time. The results demonstrate that single bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
153
0
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(160 citation statements)
references
References 34 publications
5
153
0
2
Order By: Relevance
“…Interestingly, we and others have demonstrated that nuclei of hepatocytes can be transfected very efficiently with decoy ODN. 20,21 The distribution in hepatocytes is different, with a markedly more diffuse pattern (E Fox, personal communication), which may reflect a difference in subcellular localisation, favourable for nuclear uptake. Thus uptake of decoy ODN appears to be cell type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we and others have demonstrated that nuclei of hepatocytes can be transfected very efficiently with decoy ODN. 20,21 The distribution in hepatocytes is different, with a markedly more diffuse pattern (E Fox, personal communication), which may reflect a difference in subcellular localisation, favourable for nuclear uptake. Thus uptake of decoy ODN appears to be cell type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA/DNA oligonucleotide was designed to induce a point mutation in the factor IX gene resulting in altered clotting activity. 142 Conversion rates were dose-dependent, ranged from 15% to 40% and correlated with reduction in factor IX activity. These results remained unchanged for almost 2 years and also were reproduced in a group of rats that underwent 70% partial hepatectomy 3 weeks after treatment.…”
Section: Gene Repair Strategiesmentioning
confidence: 98%
“…The feasibility of somatic cell gene targeting has been demonstrated using RNA:DNA chimaeric oligonucleotides (RDOs) or single-stranded DNA oligonucleotides (ODN) in vitro [1][2][3][4][5][6] and in vivo. [6][7][8][9][10] Gene repair has also been reported in vivo, using short DNA fragments in the lung 11 and muscle. 9,12 It is difficult to compare the efficiency of in vivo gene repair methods used by different groups, because each experimental approach is very different.…”
Section: Introductionmentioning
confidence: 99%